2011
DOI: 10.1021/jp109676b
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Effects and the Temperature Dependences of the Hyperfine Coupling Constants of Muoniated sec-Butyl Radicals in Condensed Phases

Abstract: Reported here is the first μSR study of the muon (A(μ)) and proton (A(p)) β-hyperfine coupling constants (Hfcc) of muoniated sec-butyl radicals, formed by muonium (Mu) addition to 1-butene and to cis- and trans-2-butene. The data are compared with in vacuo spin-unrestricted MP2 and hybrid DFT/B3YLP calculations reported in the previous paper (I), which played an important part in the interpretation of the data. The T-dependences of both the (reduced) muon, A(μ)′(T), and proton, A(p)(T), Hfcc are surprisingly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…A comparison with available experiments has confirmed the existence of the cis-like conformation III by low-temperature HFCC measurements. 9,10 Thus, the WFT methods and several DFT methods in group III (Fig. 1d) outperform other theoretical methods by being more in line with experimental results.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…A comparison with available experiments has confirmed the existence of the cis-like conformation III by low-temperature HFCC measurements. 9,10 Thus, the WFT methods and several DFT methods in group III (Fig. 1d) outperform other theoretical methods by being more in line with experimental results.…”
Section: Resultssupporting
confidence: 70%
“…As verified by a mSR experiment, the cis-like conformation does exist and carries a large value of HFCC on the b-muon. 9,10 In this regard, WFT methods outperform B3LYP-DFT methods decisively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Mu has long been used to understand nuclear quantum effects in chemical reactions including tunneling and quantized vibrations and there have been reported many studies showing very large isotope effects so far [3,4]. In particular, due to its extremely light mass and very large vibrational amplitudes, Mu-containing molecules frequently show a significantly delocalized character in molecular structures compared to hydrogen-and deuteriumcontaining molecules [5][6][7][8][9][10][11][12][13][14][15]. Alternatively, it has been reported that Mu can be localized in a very different region of the potential energy surface compared to hydrogen and deuterium cases due to multi-dimensional effects.…”
Section: Introductionmentioning
confidence: 99%